Makeup application based on skin colour - Nurul Ahzani, Roslan (2019)
Nowadays, there are some women they still did not know how to makeup. It is because they do not know which shade that is suitable to their skin tone. Makeup application is an application that can be as a guidance to user to choose makeup wisely. This application already sorts the shades of makeup based on skin tone. This application consists of four types of skin tone such as fair skin, medium skin, medium dark skin and dark skin. In each skin tone, user will be given two types of makeup which are lipstick and blusher. This application also will be given to choose look either neutral or night The objective of this application is to study and identify the existing application in market, to design and develop a prototype for makeup application as a guidance for user to choose the right shade based on skin tone and to evaluate the effectiveness of this application for user. Rapid Application Development (RAD) is the methodology used to develop this application. RAD consists of four phases. First is requirement planning, followed by user design, construction and lastly is cutover. After finished development, client will be given the user acceptance test (UAT) to ensure that all the function work according to requirement without any error.